Better safe than sorry: a vehicular traffic re-routing based on traffic conditions and public safety issues - Souza, Allan M. de; Braun, Torsten; Botega, Leonardo C. [UNESP]; Cabral, Raquel; Garcia, Islene C.; Villas, Leandro A. (Springer, 2019)
Vehicular traffic re-routing is the key to provide better traffic mobility. However, taking into account just traffic-related information to recommend better routes for each vehicle is far from achieving the desired requirements of proper transportation management. In this way, context-aware and multi-objective re-routing approaches will play an important role in traffic management. Yet, most procedures are deterministic and cannot support the strict requirements of traffic management applications, since many vehicles potentially will take the same route, consequently degrading overall traffic efficiency. So, we propose an efficient algorithm named as Better Safe Than Sorry (BSTS), based on Pareto-efficiency. Simulation results have shown that our proposal provides a better trade-off between mobility and safety than state-of-the-art approaches and also avoids the problem of potentially creating different congestion spots.
Keywords: Vehicular traffic re-routing; Intelligent transportation system; Vehicular ad hoc networks